2019
DOI: 10.3899/jrheum.181214
|View full text |Cite
|
Sign up to set email alerts
|

Are Target Urate and Remission Possible in Severe Gout? A Five-year Cohort Study

Abstract: Objective.Determine the proportion of patients achieving target serum urate (SU), defined as < 6 mg/dl for patients with non-severe gout and < 5 mg/dl for patients with severe gout, as well as the proportion of patients achieving remission after 5 years of followup.Methods.Patients from the Gout Study Group (GRESGO) cohort were evaluated at 6-month intervals. Demographic and clinical data were obtained at baseline. Visits included assessments of serum urate, flares, tophus burden, health-related quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…During follow-up, an sUA value of <360µml/L was numerically more frequently reached in the more ambitious approach by 83% versus 74%, but differences were not statistically significant. 28 In a Mexican study, the target sUA was achieved in only 50%-70% after 3-4 years in spite of regular visits, 29 and response rates by 12 months among general practitioners in the UK with sUA <360 µmol/L were 45%. 30 Table 2 Serum urate levels and frequency of target achievement (sUA <360 µmol/L) in patients assessed during time points.…”
Section: Discussionmentioning
confidence: 96%
“…During follow-up, an sUA value of <360µml/L was numerically more frequently reached in the more ambitious approach by 83% versus 74%, but differences were not statistically significant. 28 In a Mexican study, the target sUA was achieved in only 50%-70% after 3-4 years in spite of regular visits, 29 and response rates by 12 months among general practitioners in the UK with sUA <360 µmol/L were 45%. 30 Table 2 Serum urate levels and frequency of target achievement (sUA <360 µmol/L) in patients assessed during time points.…”
Section: Discussionmentioning
confidence: 96%
“…This observation supports the need for a longitudinal assessment of gout remission over a 12-month interval. In previous studies, a variable percentage of patients, ranging from 9.1 to 48.2% [6,44,45], reached the 2016 remission criteria [7]. This heterogeneity can be explained by several factors: first, the inclusion of patients with different clinical and laboratory characteristics (e.g., presence/absence of subcutaneous tophi and different disease duration); second, the use of different ULTs (e.g., allopurinol, febuxostat and pegloticase); third, the duration of ULT prior to the enrolment; and finally, the length of the observational period (from 12 to 60 months) [5,43,44].…”
Section: Discussionmentioning
confidence: 98%
“…This heterogeneity can be explained by several factors: first, the inclusion of patients with different clinical and laboratory characteristics (e.g., presence/absence of subcutaneous tophi and different disease duration); second, the use of different ULTs (e.g., allopurinol, febuxostat and pegloticase); third, the duration of ULT prior to the enrolment; and finally, the length of the observational period (from 12 to 60 months) [5,43,44]. Interestingly, Alvarado-de la Barrera and colleagues found that the proportion of patients achieving the remission increased with the duration of ULTs [45]. In fact, 9.1%, 30%, and 39% of patients with a non-severe tophaceous gout (less than 4 subcutaneous tophi) were in remission after 12, 24, and 48 months, respectively [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remission and cure are, thus, different aims. In the report by Alvarado-de la Barrera, et al 2 , in this issue of The Journal, recently developed Preliminary Criteria for the Remission of Gout -which have not undergone further validation -have been applied to patients with gout attending a tertiary center in Mexico. The characteristics of these patients have been described previously 3 as coming from a low socioeconomic background and being particularly noncompliant, having poorly managed, very severe gout, and treating their symptoms with self-prescribed glucocorticoid monotherapy 4 , a therapy associated to the early appearance of tophi 5,6 .…”
Section: Is Remission a Valid Target For Gout?mentioning
confidence: 99%